Can ISO 38200:2018 Wood and Wood Based Product Chain of Custody Increase Businesss Competitiveness of Wood Industries in West Java ? - Agus Purwanto; Masduki Asbari; Priyono Budi Santoso (Fakultas Kehutanan, Universitas Hasanuddin, 2019)
The purpose of this study was to determine the effect of the implementation of new standard ISO 38200:2018 to business performance and competitiveness for wood industries in west java. This research was conducted in several companies that use woods as raw material in west java of Indonesia with 180 respondents of companies that have plan to implement the ISO 38200:2018. The research background is due to lack of research on the benefits of ISO 38200:2018 in wood companies in West Java Province of Indonesia. The data collection was carried out by distributing electronic questionnaires on september until november 2019 and analyzing data processing use Structural Equation Model (SEM) and software Linear Structural Model (LISREL) version 8.70. The results of analysis show that the implementation of ISO 38200:2018 has significantly influenced business performance and competitiveness such as increase customer satisfaction index, increase sales, increase productivity and safety and employee satisfaction.